Born entrepreneurs, born leaders : how your genes affect your work life - Shane, Scott. 4 0 16; 5 (New York : Oxford University Press, 2010)
Asserting that humans' job choices, workplace behavior and professional destinies are influenced by their genetic and hormonal makeup, the author argues that individuals might bevariously hardwired to be altruistic, to job-hop, desire high-powered careers, take risks, and manage in highly idiosyncratic styles.
Introduction -- DNA at work: your genes and organizational behavior -- Why that job? The genetic foundations of your work interests -- Happy at work? How your genes affect your job satisfaction -- Instinctive choices: genetic influences on decision making -- DNA at the office: how your genes affect your management style -- Born leaders? How your genes influence your approach to leadership -- Creative genius? Your genetic dispoistion for creativity and innovation -- Born entrepreneurs? How your genes affect your tendency to start companies -- Good workers, bad workers: how your genes influence your jobperformance and your income -- Your genes matter! So what?
Includes bibliographic references and index.
Professional.
Keywords: 2 -- 0; 6; Behavior genetics.;Genetics.;Psychology, Industrial.;Applied psychology; 20; 2